2008
DOI: 10.1590/s0102-36162008001100006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação funcional do reparo artroscópico das lesões completas do manguito rotador associado a acromioplastia

Abstract: Avaliação funcional do reparo artroscópico das lesões completas do manguito rotador associado a acromioplastia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
(35 reference statements)
2
18
0
2
Order By: Relevance
“…In our study, we found that 90% of the results were satisfactory, among which 58% were excellent and 32% were good, according to the UCLA functional scale. This satisfaction index was similar to what was found in the literature (1,7,8,(21)(22)(23)(24)(25)(26) . Although our results were similar to what was found in the literature, two of the four cases that suffered renewed tearing of the supraspinatus (as shown by magnetic resonance imaging) presented unsatisfactory functional results, with complaints of pain and dissatisfaction with the results.…”
Section: A B C Dsupporting
confidence: 89%
“…In our study, we found that 90% of the results were satisfactory, among which 58% were excellent and 32% were good, according to the UCLA functional scale. This satisfaction index was similar to what was found in the literature (1,7,8,(21)(22)(23)(24)(25)(26) . Although our results were similar to what was found in the literature, two of the four cases that suffered renewed tearing of the supraspinatus (as shown by magnetic resonance imaging) presented unsatisfactory functional results, with complaints of pain and dissatisfaction with the results.…”
Section: A B C Dsupporting
confidence: 89%
“…Anatomical studies on cadavers have shown that degeneration of the rotator cuff is a normal process of human aging (11,(17)(18)(19) . However, the etiological factors involved in rotator cuff injuries in young patients differ from those in elderly individuals (18,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Embora haja elevados índices de recidivas o tratamento por meio do reparo cirúrgico aberto ou artroscópico das lesões extensas do MR possui resultados consideráveis (24) .…”
Section: Tratamento Conservador E Cirúrgico Nas Lesões Do Manguito Rounclassified